Boj proti bakterijski odpornosti - Zorman, Maša (Farmacevtski vestnik, 2025)
Type II topoisomerases are important targets for antibacterial therapy. The first inhibitors of type II topoisomerases, quinolones and aminocoumarins, emerged more than half a century ago, but their use is now in slow decline due to toxic side effects, low effectiveness and emergence of bacterial resistance. Innovations in this field – improvement of already existing classes of antibacterials and discovery of novel classes of compounds, are essential for overcoming resistance and maintaining topoisomerases as viable targets. In this paper, we present various classes of bacterial topoisomerase inhibitors, their advantages and shortcomings, as well as future perspectives.
Keywords: aminokumarini; Bakterijska rezistenca; kinoloni; novi zaviralci bakterijskih topoizomeraz; protibakterijska terapija; zaviralci topoizomeraze tipa II